RETRACTED: Impact Analysis of Meditation on Physiological Signals - Rahul Ingle; R N Awale (Society of Visual Informatics, 2018)
RETRACTEDFollowing a rigorous, carefully concerns and considered review of the article published inÂ JOIV : International Journal on Informatics Visualization to article entitled â€œImpact Analysis of Meditation on Physiological Signalsâ€ Vol 2, No 1, pp. 31-36, January 2018, DOI:Â https://doi.org/10.30630/joiv.2.1.98This paper has been found to be in violation of theÂ JOIV : International Journal on Informatics Visualization Publication principles and has been retracted.The article contained redundant material, the editor investigated and found that the paper published inÂ Ahani, A., Wahbeh, H., Miller, M., Nezamfar, H., Erdogmus, D., & Oken, B. (2013). Change in physiological signals during mindfulness meditation.Â International IEEE/EMBS Conference on Neural Engineering : [proceedings]. International IEEE EMBS Conference on Neural Engineering, 1738â€“1381. https://doi.org/10.1109/NER.2013.6696199The document and its content has been removed from JOIV : International Journal on Informatics Visualization, and reasonable effort should be made to remove all references to this article.